QuantiFERON-TB Gold Plus evaluation for latent tuberculosis infection among Italian healthcare workers: a cross-sectional study (Epidemiology, Biostatistics, and Public Health, 2022)
Background: healthcare workers (HCWs) are at higher risk of being exposed to tuberculosis (TB). The aim of this study was to estimate LTBI prevalence and evaluate associated risk factors among Italian HCWs using a new generation IGRA test, Quantiferon Plus (QTF-Plus), providing also an analytical evaluation of this test.Methods: this cross-sectional study was conducted during the annual health surveillance program performed in 2017, evaluating 1470 HCWs of a teaching hospital in Rome, tested with QTF-Plus. A standardized questionnaire was collected for multivariate risk analysis. The independent variables associated with a higher frequency of LTBI were tested in a multivariate logistic regression model.Results: LTBI was diagnosed in 50 out of 1470 (3.4%) of HCWs. The male gender and age>40 years were significantly associated with the risk of LTBI. The levels of interferon-γ were significantly lower in subjects with a recent conversion than in those with an older positivity. Moreover, interferon-γ values exceeding 8 IU/ml were recorded in 8 out of 35 remote subjects but in no recent subjects. The concordance between TB1 and TB2 results was 88%, while in 6 out of 50 subjects we found a discrepancy.Conclusion: the LTBI condition among Italian HCWs was very low. In subjects with discordant outcomes between TB1 and TB2, especially when the test values are close to the cut-off, is recommended a repetition of the test to confirm its positivity.Key words: tuberculosis, latent tuberculosis infection, interferon-gamma release assay, quantiferon plus, healthcare workers
Keywords: tuberculosis; latent tuberculosis infection; interferon-gamma release assay; quantiferon plus; healthcare workers